Long-term quality of life after endovac-therapy in anastomotic leakages after esophagectomy - Heits, Nils; Bernsmeier, Alexander; Reichert, Benedikt; Hauser, Charlotte; Hendricks, Alexander; Seifert, Dana; Richter, Florian; Schafmayer, Clemens; Ellrichmann, Mark; Schniewind, Bodo; Hampe, Jochen; Becker, Thomas; et al. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Endoluminal vacuum therapy (EVT) has been successfully established with promising survival rates in the treatment of anastomotic leakages after esophagectomy. It is still unclear how this therapy affects health related quality of life (HRQOL). Methods: HRQOL was prospectively assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ-C30) questionnaire. Assessment was carried out prior to surgery, after discharge, 6 months and 12 months after surgery. We compared HRQOL after EVT (n=23) to patients without anastomotic leakages as a control group (n=50). Investigated parameters included age, sex, and localization of anastomosis, number of EVT sessions, length of ICU and hospital stay, therapy failure, anastomotic stricture, tumour stage, neoadjuvant and adjuvant treatment, sepsis. Results: After esophagectomy HRQOL increased within 12 months. Compared to patients without leakages the EVT-group showed significantly better HRQOL-scores for pain, social and emotional functioning after discharge and 6 months after surgery. In the long-term follow up HRQOL was comparable between the groups. After EVT age, advanced tumour stage, tumour recurrence, anastomotic strictures, length of ICU and hospital stay and length of EVT had a significant influence on HRQOL. Conclusions: EVT is a promising therapeutic option in leakages after esophagectomy. In the long-term, HRQOL of EVT-treated patients is comparable to patients, who did not suffer from postsurgical leakages.